Pengaruh Penggunaan Pupuk Nanosilika Terhadap Pertumbuhan Tanaman Tomat (Solanum lycopersicum) var.Bulat - Fitriani, Harmigita Putri; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Tomato (Solanum lycopersicum var Bulat) is one of commodity that itâ€™s demand always increase every year. Further more, the stock of tomato always not enough to market demand.Â Due to this problem, the productivity have to increased by nanosilica fertilizer. Nanosilica fertilizer contain micronutrient of Si that important to plant growth. This research aim to analyze the effect of Nanosilica fertilizer to the growth of Solanum lycopersicum var Bulat. This research was used Completely Randomized Design with 4 treatment, each replicated 3 times. The concentration of nanosilica fertilizer was applied in 3 different concentration, 25 %, 50 %, and 75 %. Parameter that was observed are the plant height, the number of leaf, the root height, and the fresh weigth of plant. The result showed that the growth optimalized by nanosilica fertilizer in 75 % concentration. Â Keyword : tomato, nanosilica, the growth